2010
DOI: 10.1016/j.socscimed.2010.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of, and attitudes towards, pregnancy and fatherhood amongst incarcerated young male offenders: Findings from a qualitative study

Abstract: Teenage parenthood is problematised in the UK. Attention is increasingly falling on the potential or actual father yet we still know relatively little about young men's experiences and attitudes in this area. This paper focuses on the experiences of, and attitudes towards, pregnancy and fatherhood amongst a sample of men incarcerated in a Scottish Young Offender Institute. In-depth interviews were conducted with 40 inmates, aged 16 -20, purposively sampled using answers from a questionnaire administered to 67 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 14 publications
0
43
0
1
Order By: Relevance
“…69 There may, however, be other aspects too. For instance, a range of ideas about responsibility for pregnancy exist, [70][71][72][73][74][75] there appears to be an ideal of financial stability as a pre-requisite for pregnancy planning, 72,76,77 and there is a possible pejorative discourse of unintended pregnancy as entrapment among a minority of men. 69,71 Our sample included two female partners.…”
Section: Discussionmentioning
confidence: 99%
“…69 There may, however, be other aspects too. For instance, a range of ideas about responsibility for pregnancy exist, [70][71][72][73][74][75] there appears to be an ideal of financial stability as a pre-requisite for pregnancy planning, 72,76,77 and there is a possible pejorative discourse of unintended pregnancy as entrapment among a minority of men. 69,71 Our sample included two female partners.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the men’s desires to be “good fathers” should be noted. Young incarcerated men appear to aspire to being caring fathers: warm, sensitive, attentive, protective of their child, and spending time with and supporting him/her (Buston, 2010 ; Buston, O’Brien, & Maxwell, in preparation ). All of the fathers participating in the two deliveries observed for this study said that they wanted to be good fathers.…”
Section: Discussionmentioning
confidence: 99%
“…Buston (2010) found that some of the incarcerated men in their study did not question their lack of power in the decision-making process. Buston (2010) highlights that pregnancies tended to be seen as the property of the female partner, reflecting both the power of the female partner to claim a pregnancy as her own, and the power of the male partner to be able to leave the consequences of sex largely to the woman. Deslauriers (2011) in a qualitative study with young fathers in Quebec found that the young fathers did not play a role in the decision to bring the pregnancy to term.…”
Section: Adolescent Men's Involvement In Pregnancy Decision-makingmentioning
confidence: 99%